PENGARUH HARGA DAN PROMOSI MELALUI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN PADA BUTIK DI KOTA METRO LAMPUNG - Ardiansyah Japlani (Universitas Muhammadiyah Metro Lampung, 2020)
The emergence of various kinds of Butiks that sell some of the same fashion products but with different prices, good promotions and prices that match the quality of the products offered will affect the purchase decision. The purpose of this study was to determine the significant effect of price and promotion through social media on purchasing decisions at Butik Stores in Metro Lampung City(GnE Butik, Amie Butik, Harmua Queen, Butik Ariesta, Nanda Butik, Klik Shop Butik, Ra Butik). In this study using primary data and secondary data, the research method used was accidental sampling with a sample size of 100 people. The data analysis technique used is validity test, reliability test, normality test, linearity test and homogeneity test. Testing the analysis model in this study using multiple linear regression analysis, T test, F test and R determination. Based on the results using the T test, it was found that the price had a significant effect on purchasing decisions at Butik Stores in Metro Lampung City and promotions through social media had a significant effect on purchasing decisions at BoutiqueStores in Metro Lampung City. From the F test, prices and promotions through social media simultaneously have a significant effect on purchasing decisions at Butik Stores in Metro Lampung City. This study is aimed at implementing future marketing strategies at Boutiques in Metro City.Keywords: Price, Promotion, Social Media, Purchasing Decision